Benefit Sharing Mechanism for Operationalization of REDD+ in India - Jha, Shashidhar Kumar; Sinha, Bhaskar (Indian Forester, 2017)
The appropriate mechanism for equitable sharing of REDD+ benefits is challenging. Only a few REDD+ pilot projects are formulated in the globe with benefit sharing mechanism. There is no single standardized benefit sharing mechanism or framework for REDD+ formulated anywhere in the world till date. The present study was proposed to formulate a benefit sharing mechanism of REDD+ in India. The basis for compensation of REDD+could be enhancement in carbon stock or growing stock. The state or forest with lesser potential of productivity due to climate factors can be compensated further through other government funds in order to overcome the discrepancy. India’s submission to UNFCCC emphasized that sharing of benefits would be at four levels i.e. international to national; national to sub-national; sub national to division level and division to village/community/landholder. The total benefit of REDD+ is proposed to be divided into 80:20 ratio with 20%as earmarked for the government institutions at national, state and division levels as transaction cost and/or for strengthening institutions towards monitoring and implementation REDD+ activities. The rest of 80% fund should be distributed amongst the stakeholders contributing to enhancement of carbon stocks. The REDD+ cell in co-ordination with state/district/division level agencies/officials should distribute the benefits after validation of enhancement in carbon stock.